Hyperplastic Breast Anomalies in the Female Adolescent Breast - Wolfswinkel, Erik M.; Lemaine, Valerie; Weathers, William M.; Chike-Obi, Chuma J.; Xue, Amy S.; Heller, Lior (Seminars in Plastic Surgery, 2013)
Macromastia in adolescents is multifactorial and usually idiopathic, associated with obesity or hormonal imbalances. Less commonly, it can result from virginal or juvenile breast hypertrophy, a rare condition of unknown etiology, where an alarmingly rapid breast enlargement occurs during puberty. Breast hypertrophy in the adolescent population can have significant long-term medical and psychological impacts. Although symptoms can be severe, many plastic surgeons, pediatricians, and parents are often reluctant to surgically treat adolescent macromastia. However, reduction mammoplasty is a safe and effective treatment and may be the only way to alleviate the increased social, psychological, and physical strain caused by macromastia in adolescents.
Keywords: adolescent; macromastia; juvenile breast hypertrophy; reduction mammoplasty